HER2 Positivity Is Affected by the Papillary Structure and Has a Bidirectional Prognostic Value for Gallbladder Carcinoma - Chen, Lingli; Xu, Lei; Shen, Licheng; Luo, Rongkui; Jiang, Dongxian; Wang, Yueqi; Li, Wei; Hou, Yingyong (Frontiers in Genetics, 2022)
Gallbladder carcinoma (GBC) is responsible for 80-95% of biliary tract malignancies and has a dismal prognosis. Human epidermal growth factor receptor 2 (HER2) is a promising therapeutic target of GBC. Through immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) methods, HER2 expression and gene amplification were identified on high-output tissue microarrays (TMAs) developed in 306 GBC cases to investigate its relationship with GBC and clinicopathological characteristics. Adenocarcinomas accounted for 223 (72.9%) of the cases, with 62 (27.8%) being papillary adenocarcinoma or having partial papillary structure. HER2 positivity was studied in 16.1% (36/223) of patients with adenocarcinoma and 41.9% (26/62) in adenocarcinoma with papillary structures. For 143 radically-resected primary GBC cases with 24 HER2-positive tumors, survival data were valid; the median survival time was not reached, and the 5-year survival rate was 52.9%. All patients in stage 0-Ⅰ survived, and the results of the HER2-positive group and the stage II HER2-negative group were similar (P=0.354). However, in stage III, the mortality rate in the HER2-positive group was reduced (P=0.005), and the mortality rate in stage IV was higher (P=0.005). In conclusion, HER2 positivity was significantly higher in patients with papillary GBC. The predictive value of HER2 varies by the clinical stage, with no prediction in the early stages, better in stage III, and worse in stage IV.